Ecological Study and Habitat Characteristics of Sea Cucumbers (Holothuroidea) in Kamal and Socah Waters, Bangkalan Regency, Madura, Indonesia - Pramithasari Febi Ayu; Triajie Haryo; Wardhana Arinda Widya (BIO Web of Conferences)
Sea cucumbers are economically valuable commodities in Bangkalan waters and play a crucial ecological role in marine ecosystems. Understanding their habitat characteristics and ecological health is essential for sustainable management and conservation. This study aims to assess the ecological health and habitat characteristics of sea cucumbers in Kamal and Socah waters of Bangkalan Regency, Madura, Indonesia. Sea cucumbers were collected using hand collection methods during low tide. Water quality and substrate conditions at the collection sites were evaluated to ensure suitability for sea cucumbers. The study identified four sea cucumber species: Phyllophorus sp., Phyllophorella spiculata, Acaudina leucoprocta, and Colochirus quadrangularis. Diversity indices were low (<1), with Kamal ranging from 0.2 to 0.86 and Socah from 0 to 0.87. Dominance values were medium to high (0.5-1), except in Socah area 5 where dominance was low (0.48). Phyllophorus sp. was the most dominant species, comprising 58% of the total biota in both locations. The low diversity and varying dominance of sea cucumber species are attributed to the sandy sediment and suitable water quality in both locations. These findings highlight the need for continued monitoring and management to ensure the sustainability of sea cucumber populations in Bangkalan waters.